Potret Subordinasi Perempuan Dalam Pendidikan - Surjanto, Agus Eko (Musawa Jurnal Studi Gender dan Islam, 2008)
The curriculum, both in religious and secular educations, generally tends to emphasize men's role in public spheres and highlights women's role in domestic arena. The content of curriculum, for instant, contains gender biased pictures, sentences or illustrations. The curriculum in religious education is also similar: there is an obvious tendency to maintain gender bias due to the authors' conviction that the books they refer to (fiqih books) are sacred, already final and unchangeable. Religious text books, thus, tend to maintain women subordination. In order to develop gender sensitive religious understanding, then, there is a need to revise religious text books that include gender bias. The revision is important because this gender biased religious understanding has become common understanding in society. This is because Muslim society attempt to understand their religious teachings dogmatically. They do not use a critical approach in understanding religious norms particularly the ones they accommodate in the text books related to women's status and role.